The educational world in the new changes that are developing ... - Belso Perez, Estefanía (Avances en Supervisión Educativa, 2013)
Facing the new paradigms, humanity must learn to be swayed by the heart and not by the head as we have done so far. If we accept that fact, education requires a new line of action in which students are considered Human Beings with the need for development that allows them to have a life experience stemming from the consistency and honesty, with sense, direction and plenitude.